ANALISIS IMPLIKASI HUKUM PERJANJIAN KERJA WAKTU TERTENTU YANG DIBUAT SECARA TIDAK TERTULIS: MELALUI PENDEKATAN HUKUM PROGRESIF - Fadillah, Azyra; Pratama, Rio Arif (Gapenas Publisher, 2025)
This study examines the legal implications of fixed-term employment contracts (PKWT) made without written agreements through a progressive law approach. The primary concern addressed is the legal vacuum and uncertainty caused by the absence of sanctions for unwritten PKWT, as stipulated in the amendments to Article 57 of Law Number 6 of 2023 concerning Job Creation. This study aims to analyze the legal implications of unwritten PKWT and seek progressive law-based solutions that prioritize workers justice. This research employs a normative juridical approach, utilizing a legislative approach and analysis of progressive law doctrine. The findings indicate that unwritten PKWT lead to legal uncertainty for workers, particularly in pursuing their rights and resolving industrial relations disputes. This is due to the lack of consequences for non-compliance with Article 57, resulting in a legal vacuum. From a progressive law perspective, an alternative solution emerges by prioritizing substantive justice over legal formalities, providing better protection for workers. This approach also highlights the need to strengthen regulations to ensure PKWT implementation aligns with the principles of justice.